Enhancing third-party software reliability through bug bounty programs - ZHOU, Tianlu (Institutional Knowledge at Singapore Management University, 2023)
Bug Bounty Programs (BBPs) reward external hackers for identifying and reporting software vulnerabilities. As the number of security issues caused by third-party applications has been significantly increased recently, many digital platforms are considering launching BBPs to help enhance the reliability of third-party software. BBPs bring benefits to the platform and vendors, meanwhile impose additional costs on them as well. As a result, the overall impact of using BBP is unclear. In this paper, we present an analytical model to examine the strategic decisions of launching and participating in a BBP for the platform and the third-party vendor, respectively. We find that the platform’s (the vendor’s) BBP launching (participation) decisions depend on two key factors: the expected loss due to security breaches and the vendor’s initial reliability investment efficiency. We show that the incentive of using BBP, for the platform and vendor, sometimes is inconsistent.